Autoridad poética y tradición literaria en Herondas (mimo VIII) y Teócrito (Idilio 7) - Fernández, Claudia N. (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2007)
The aim of this article is to examine the similarities between Theocritus’ Seventh Idyll —«The Thalysia»— and the fragmentary mime VIII of Herondas —«A Dream»— and, according to the custom of Hellenistic poets to allude to their coetaneous’ poetry, it suggests the hypothesis that the mime of Herondas reports the influence of Theocritus’ Idyll. This circumstance allows us to explain some of the more controversial passages of the mime: the rustic disguise the author chose to present himself in the dream’s tale, the country setting, the presence of other enigmatic herdsmen, even the poem’s unusual framed pattern. It also proposes to interpret the Seventh Idyll with the experience of having read Herondas.